2016
DOI: 10.1039/c5ra24039e
|View full text |Cite
|
Sign up to set email alerts
|

Use of morphological features of carbonaceous materials for improved mechanical properties of epoxy nanocomposites

Abstract: The mechanical properties of epoxy nanocomposites can be significantly altered by tailoring the morphological features of carbonaceous fillers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 58 publications
0
31
0
Order By: Relevance
“…In addition, topography and morphology of the filler also influence the mechanical properties of nanocomposites. Atif et al showed that a wide particle size distribution yields an effective reinforcement as the empty spaces created by the larger particles can be occupied by the smaller particles thereby resulting in a strong network of the filler and a concomitant increase in the mechanical properties [143]. A uniform dispersion of the filler in the matrix is the most important issue.…”
Section: Reviewmentioning
confidence: 99%
“…In addition, topography and morphology of the filler also influence the mechanical properties of nanocomposites. Atif et al showed that a wide particle size distribution yields an effective reinforcement as the empty spaces created by the larger particles can be occupied by the smaller particles thereby resulting in a strong network of the filler and a concomitant increase in the mechanical properties [143]. A uniform dispersion of the filler in the matrix is the most important issue.…”
Section: Reviewmentioning
confidence: 99%
“…In PMCs, thermosetting epoxy is the most commonly used matrix [4][5][6][7]. The damage tolerance and fracture toughness of epoxy can be enhanced with the incorporation of (nano-) fillers such as metallic oxides [8][9][10], clays [11][12][13], carbon nanotubes (CNTs) [14][15][16], and other carbonaceous materials [17][18][19]6,5].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from that, graphene based materials has been used is different fields such as composites and coatings, electronics devices, energy storage, sensors and biomedical applications [20]. Atif et al in their study reported that MLG improved Young's modulus and microhardness by 25.7% and 18.3%, respectively [24]. The MLG also increased Tg and storage modulus compared to unfilled epoxy [25][26][27].…”
Section: Introductionmentioning
confidence: 97%